Historic Wooden Shipwrecks Influence Dispersal of Deep-Sea Biofilms - Moseley, Rachel D.; Hampel, Justyna J.; Mugge, Rachel L.; Hamdan, Leila J. (Frontiers in Marine Science, 2022)
Wood arrives on the seabed from natural and anthropogenic sources (e.g., wood falls and wooden shipwrecks, respectively) and creates seafloor habitats for macro-, meio- and microbiota. The way these habitats shape microbial communities and their biogeographic patterns in the deep sea requires study. The objective of this work was to investigate how historic wooden-hulled shipwrecks impact the dispersal of wood-colonizing microbial biofilms. The study addressed how proximity to wooden shipwrecks shapes diversity, richness, and community composition in the surrounding environment. Study sites included two historic shipwrecks in the northern Gulf of Mexico identified as wooden-hulled sailing vessels dating to the late 19th century. Two experimental microbial recruitment arrays containing pine and oak samples were deployed by remotely operated vehicle proximate (0–200 m) to each shipwreck and used to establish new wooden habitat features to be colonized by biofilms. The experiments remained in place for approximately 4 months, were subsequently recovered, and biofilms were analyzed using 16S rRNA gene amplification and sequencing for bacteria and archaea and ITS2 region amplification and sequencing for fungi to determine alpha diversity metrics and community composition. The work examined the influence of wood type, proximity to shipwrecks, and environmental context on the biofilms formed on the surfaces. Wood type was the most significant feature shaping bacterial composition, but not archaeal or fungal composition. Proximity to shipwrecks was also a significant influence on bacterial and archaeal composition and alpha diversity, but not on fungal communities. In all 3 domains, a peak in alpha diversity and richness was observed on pine and oak samples placed ~125 m from the shipwrecks. This peak may be evidence of an ecotone, or convergence zone, between the shipwreck influenced seabed and the surrounding seafloor. This study provides evidence that historic wooden shipwrecks influence microbial biofilm dispersal in the deep sea.